Nutritional Content and Characteristics of Antimicrobial Compounds from Fermented Oil Palm Fronds (Elaeis guineensis Jacq.) - Dewi Febriana; Syukria Ikhsan Zam; Rahmi Febriyanti; Zumarni Zumarni; Jepri Juliantoni; Abdul Fatah (Journal of Tropical Life Science, 2020)
This research was conducted to determine physical quality, the nutritional quality and characteristics of antimicrobial compounds from fermented oil palm fronds (FOPF). This research was carried out using a Complete Randomized Design with 4 treatments and 4 replications. The following treatments were performed by the addition of different additives namely: 10% poultry manure, 10% cow feces, 5% urea and 5% molasses. All treatments were extracted in stages using n-hexane, ethyl acetate and methanol. The observed parameters were physical quality (pH, aroma, color, and texture), nutritional quality (neutral detergent fiber (NDF), acid detergent fiber (ADF), hemicellulose, cellulose and lignin), yield of extract, class of bioactive compounds and the antimicrobial activity test of extracted compounds. The data were analyzed using a one-way analysis of variance and differences between treatments were tested using Duncan's multiple range test. The addition of different additives has a very significant effect (P < 0.01) on the lignin content; significant effect (P < 0.05) on pH, aroma, color and texture; and no effect on the content of NDF, ADF, hemicellulose and cellulose. The highest yield of extract was obtained from methanol extract with the addition of poultry manure. The methanol extract on the addition of poultry manure and urea were identified as compounds in the steroid, tannin and phenolic classes. The highest antimicrobial activity test against Escherichia coli (12.83 mm) was obtained from FOPF extract (1%) with addition of poultry manure, while highest antimicrobial activity test against Staphylococcus aureus (11.67 mm) was obtained from FOPF extract (4%) with addition of molasses. The conclusion of this research was FOPF with addition of poultry manure provides good physical quality, nutritional quality and can inhibit the growth of E. coli and S. aureus at a concentration of 1%.